Synthesis, Characterization and Electrochemical Studies on the Interaction Mechanism between Copper(II) Complex and DNA - Ling Zhang, Xiu; Guo, Feng (Asian Journal of Chemistry, 2010)
The Cu(II) Schiff base was synthesized and characterized by elemental analysis, molar conductivity, IR and thermal decomposition. Cyclic voltammetry was used to investigate the interaction between [Cu(GNA)(H2O)]·H2O (where GNA = glycine) and DNA. The complex had excellent electrochemical activity on the glassy carbon electrode (GCE) with a couple quasi-reversible redox peaks. In 0.05 M Britton-Robinson (B-R) buffer solution (pH 4.86), the binding ratio between [Cu(GNA) (H2O)]·H2O and DNA was found to be 1:1 and the binding constant was 1.67 × 104 L mol-1.